2002
DOI: 10.1063/1.1519962
|View full text |Cite
|
Sign up to set email alerts
|

Preferential carbon etching by hydrogen inside hexagonal voids of 6H-SiC(0001)

Abstract: Characterization of hydrogen etched 6H-SiC(0001) substrates and subsequently grown AlN films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, the EGS observed here differ from exfoliated graphene bubbles reported previously [43] in a number of important ways; firstly, the identification of the exfoliated bubbles was done using optical microscopy with the use of Newton rings; however, due to the lower height of our EGS compared to the bubbles reported in [51,52], the Newton rings cannot be observed. Secondly, the characteristic dimensions of our EGS are smaller and orders of magnitude lower in height (≈1%) than those described in [52,32].…”
Section: Surface Morphology: Identification Of Epitaxial Graphene Nan...mentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, the EGS observed here differ from exfoliated graphene bubbles reported previously [43] in a number of important ways; firstly, the identification of the exfoliated bubbles was done using optical microscopy with the use of Newton rings; however, due to the lower height of our EGS compared to the bubbles reported in [51,52], the Newton rings cannot be observed. Secondly, the characteristic dimensions of our EGS are smaller and orders of magnitude lower in height (≈1%) than those described in [52,32].…”
Section: Surface Morphology: Identification Of Epitaxial Graphene Nan...mentioning
confidence: 55%
“…These circles could not be attributed to the simple roughness of the surface, i.e. 0.5-2 nm, commonly observed for epitaxial graphene grown on 4H-SiC substrates [46,50,51], or defects due to their large size and location, far from terrace intersections. These features were further studied by supplementing AFM topography with simultaneous UFM nanomechanical mapping (figure 3), where the lateral resolution is maintained at approximately 2 nm.…”
Section: Surface Morphology: Identification Of Epitaxial Graphene Nan...mentioning
confidence: 90%
“…Well controlled sequent KOH etching (tracking etching) is suitable for detailed analysis of the nature and interactions of defects in SiC epitaxial layers [11,12]. High temperature etching in the vapour of KOH [13], in hydrogen [14] and in molten Si [5] enables also study of extended defects in SiC, but these techniques seem to be less convenient due to more demanding technical requirements.…”
Section: General Remarksmentioning
confidence: 99%
“…The observed electrical properties are significantly affected by doping and other parameters (e.g., stain, flake edges). Raman spectroscopy is a powerful technique to investigate graphene quality and doping [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Therefore, it is extremely informative to correlate Raman spectra with corresponding electrical behavior in graphene samples.…”
Section: Raman Investigation Of Electrical Properties In Epitaxialmentioning
confidence: 99%
“…Specifically, it was found that the Raman shift of the G band behaves symmetrically for equal electron and hole doping percentages around a doping minimum [ 115 ]. In addition, it was shown that the G band FWHM is reduced as the electron/hole doping is increased [ 117 , 118 ]. This occurs due to the Pauli exclusion principle that blocks the conversion of phonons into electron–hole pairs as soon as the electron–hole gap becomes larger than the phonon energy.…”
Section: Raman Investigation Of Electrical Properties In Epitaxialmentioning
confidence: 99%